A unique role for IL-13 in inducing esophageal eosinophilia through MID-1 and STAT6 - Girkin, Jason L. N.; Sokulsky, Leon A.; Starkey, Malcolm R.; Hansbro, Philip M.; Foster, Paul S.; Collison, Adam M.; Mattes, Joerg (Frontiers in Allergy, 2023)
Introduction Eosinophilic esophagitis (EoE) is associated with allergen-driven inflammation of the esophagus and an upregulated Th2 cytokine signature. Recombinant interleukin (IL)-13 (rIL-13) administration to mice induces some of the hallmark features of EoE, including increased eotaxin expression and eosinophil recruitment. Inflammation in EoE has previously been shown to depend on the expression of TRAIL and MID-1, which reduced protein phosphatase 2A (PP2A) activity. The relationship between IL-13 and TRAIL signalling in esophageal eosinophilia is currently unknown. Objective To investigate the interaction between IL-13-driven eosinophil infiltration and TRAIL or MID-1 in the esophagus. Method We administered rIL-13 to wild type (WT), TRAIL-deficient (Tnsf10−/−) or STAT6-deficient (STAT6−/−) mice and targeted MID-1 with small interfering RNA. Results rIL-13 administration to mice increased TRAIL and MID-1 expression in the esophagus while reducing PP2A activity. TRAIL deficient, but not STAT6 deficient mice demonstrated increased MID-1 expression and PP2A reduction upon IL-13 challenge which correlated with eosinophil infiltration into the esophagus. Silencing MID-1 expression with siRNA completely ablated IL-13 induced eosinophil infiltration of the esophagus, restored PP2A activity, and reduced eotaxin-1 expression. Conclusion IL-13-driven eosinophil infiltration of the esophagus induced eosinophilia and eotaxin-1 expression in a STAT6-dependent and MID-1-dependent manner. This study highlights a novel mechanism employed by IL-13 to perpetuate eosinophil infiltration.